Antimicrobial Resistance Patterns and Metallobeta-lactamases Producing of Imipenem Resistant Pseudomonas aeruginosa Isolated from Clinical Samples of Iraqi Patients - Marwa Lafta Jebur (Journal of Global Pharma Technology, 2019)
In this study, a total of 160 clinical samples (72 burned skin, 25 wound, 18 sputum, 24 urine and 21 ear samples) were collected from five hospitals in Baghdad during the period December 2017 - April 2018. The samples were cultured on MacConkey agar and blood agar plates to isolate Pseudomonas aeruginosa in order to estimate its prevalence rate, which was 65% (104/160) of the total clinical samples. It was found that 37.5% (39/104) of P. aeruginosa isolates were resistant to imipenem (IRPA). A phenotypic detection of beta-lactamases showed that all IRPA isolates did not produce extended spectrum beta-lactamases, while 89.7% (35/39) of these isolates produced metallo-betalactamases (MBLs). Antibiotic susceptibility test against 11 antibiotics using the disk diffusion method showed that all metallo-betalactamases producing IRPA isolates were sensitive to polymyxin B, while resistance rates were 100% to both cefotaxime and ceftazidime, 94.3% to both netilmicin and amikacin, 91.4% to each of meropenem, gentamicin and tobramycin, 88.6% to cefepime, 82.9% to aztreonam and 77.1% to piperacillin/tazobactam. The resistance of metallo-betalactamase producing IRPA isolates for antibiotics according to MIC values was 100% to both tigecycline and cefazolin, 91.4% to meropenem, 85.7% to tobramycin, 80% to both cefepime and gentamicin, 71.4% to each ceftazidime, amikacin and levofloxacin, and 51.4% to ciprofloxacin.Keywords: Pseudomonas aeruginosa; Metallobeta-lactamases; and Antimicrobial Resistance.